Column drop: making CNNs invariant to image cropping - Dudar, V.V.; Semenov, V.V. (Штучний інтелект, 2018)
We introduce a new regularization technique column drop which uses inner structure of CNNs for classification to make its output invariant to random crops of input image. Use of this regularization eliminates need in data augmentation by random image cropping under some conditions on architecture of CNN. We show that application of column drop to pooling layers leads to improvement in generalization compared with use of dropout for pooling layers. В статті описано новий метод регуляризації column drop для навчання згорткових нейронних мереж для класифікації, що робить їх інваріантними до вибору підзображення. Використання такої регуляризації відкидає необхідність в розширенні навчальної вибірки зображень за допомогою вибору випадкових підзображень, за певних умов на архітектуру мережі. Застосування column drop до pooling шарів мережі призводить до покращення точності класифікації на тестовій вибірці у порівнянні з використанням методу dropout для pooling шарів.